Impact of integrated nitrogen management on nut yield and soil fertility in almond (Prunus dulcis) under north western Himalayan region of India - KUMAR, DINESH; AHMED, NAZEER; SHARMA, V K (The Indian Journal of Agricultural Sciences, 2015)
To improve nut yield and soil fertility, a study on nitrogen management was taken up on eight year old almond (Prunus dulcis L.) grafted plants of commercial variety Waris spaced at 3.5 x 3.5m and treatments were imposed in 2009. The results of long term experimentation clearly indicated that maximum mean nut yield (3.16 kg/tree and 2.71 tonnes/ha) was recorded with the application of 40 tonnes/ha FYM followed by 100% RDF + 10 tonnes/ha FYM (2.83 kg/tree and 2.41 tonnes/ha) and minimum (1.61 kg/tree and 1.73 tonnes/ha) was recorded in control plots (No fertilizer). The fertility status of soil also improved by application of organic and inorganic fertilizers, the available nitrogen, phosphorus and potassium content (46.13, 26.8, 38.67%) were estimated with the application of 40 tonnes FYM/ha in almond variety Waris under north western Himalayan region of India.